Australian inpatient cancer rehabilitation as seen by patients receiving care pre and post intervention: Insights into unmet needs in the cancer and rehabilitation journey. (12th August 2022) - Reynolds, Najwa L.; Cole, Andrew M.; Walmsley, Bruce D.; Poulos, Christopher J.
Abstract: Objective: The objective of this study is to explore both the negative and positive lived experiences of cancer survivors during specialist inpatient rehabilitation programmes. Methods: This phenomenological study explored the negative and positive perspectives of cancer survivors with residual disability, during their inpatient rehabilitation. Semi‐structured interviews conducted with 22 inpatients on admission and discharge were analysed using the protocols of Interpretative Phenomenological Analysis. Results: Experiences of inpatient cancer rehabilitation were not independent of the whole cancer trajectory. Rather, for these inpatients, processing and ruminating upon challenges to self from the moment of cancer diagnosis and throughout treatments indicated that more emotional and psychosocial support may be useful throughout cancer rehabilitation and the whole cancer trajectory. Conclusion: Understanding the concurrent sources of psychological distress and growth in these cancer survivors as they recover from life changing events provides a unique consumer evaluation of an inpatient cancer rehabilitation service and the overall cancer experience. This study has implications for developing insight into the impact that the cancer trajectory has on the individual and reinforces the importance of a holistic approach to rehabilitation that includes a supported mind, body and spirit appreciation of healing.